Peningkatan Hasil Belajar Muatan Ipa Pada Tema Peduli Terhadap Makhluk Hidup Dengan Media Permainan Ular Tangga Di Kelas Iv SD Negeri Ngawu Tahun Ajaran 2018/2019 - Suwasiti Suwasiti (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2019)
This research is motivated by the low ability of students to master material forms outsideanimals and plants as well as its function on the theme of Care for Living Creatures in class IVSDN Ngawu in 2018. Prior to the research the students' ability to master the materialespecially in the material was classically only 30% of students declared complete with anaverage of 61. Classroom action research (CAR) in this study aims to improve the ability tomaster the material so that students can be declared complete. Efforts are made to overcomethe problem is through learning by using a snake ladder game media. The research was carriedout in 2 cycles each cycle I 2x meetings and cycle II 3x meetings. The steps of implementinglearning begin with the teacher's explanation, group games, and competition. Methods of datacollection through observation, test sheets, assessment sheets and documentation. From theobservations of the results of the evaluation of learning in the research activities showed thatthe use of snakes and ladders game media can improve the ability to master the materialoutward forms of animals and plants on the theme of Caring for Living Beings of Grade IVstudents of SDN Ngawu in 2018. These results are evidenced by the increase in studentlearning outcomes in each cycle, both cycle I and cycle II. After completing the first cycle, thecompleteness level becomes 60% with an average of 73. After the improvement and reflectionin the second cycle, the completeness of learning outcomes increases to 100% with an averageof 87.Keywords: PTK, Natural Sciences, Ladder Snake